PENGARUH FREE CASH FLOW, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGES - Desi Novitasari; Mohamad Husni; Riyanthi Idayu (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
This study  aims to examine the effect of  free cash flow, profitability, liquidity and leverage on dividend policy in a simulttan (together) and partially. This research is a research with a quantitative approach. Data collection techniques are carried out based on data sources, namely secondary data, data sources can be obtained from the Indonesia Stock Exchange (IDX) www.idx.co.id.  The sampling method  uses purposive sampling method.  The number of samples in this study was 30 observations in 6 companies within a period of 5 years.  The results of this study showed that the signification value of the t test free cash flow of 0.292 > 0.05 stated that it had no effect on dividend policy, the liquidity t test result of 0.404 > 0.05 stated that it had no effect on dividend policy and the result of the t leverage test 0.567 > 0.05 stated  has no effect on dividend policy. Jointly, the signification value of hasl test f free cash flow, liquidity and leverage of 0.466 > 0.05 stated that it had no effect on the dividend policy simultaneously. The conclusion for this study is that  the variables Free cash flow (X1), Liquidity (X2), and Laverage (X3) have no effect on dividend policy (Y).